1991
DOI: 10.5144/0256-4947.1991.141
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habits of King Saud University Students in Riyadh

Abstract: The smoking habits of 2264 male students at King Saud University were investigated. Thirty-seven percent of the students smoked, and over a half smoked more than 15 cigarettes per day. Cigarettes were the main form of smoking. Most of the smokers knew about the hazards of smoking through the media and wished to stop smoking. Nonsmokers cited religious consideration and nonsmoking parents as the most important reasons for not smoking. A public health campaign is strongly recommended to reduce the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 1 publication
2
30
2
Order By: Relevance
“…This demonstrates how difficult it is to stop this habit once it is established. Other studies in Saudi Arabia 8,11,13 reached similar conclusions. A study from British General Practice 35 reported an annual cessation rate ranging from 5% to 11% following simple advice and educational leaflets.…”
Section: 22supporting
confidence: 75%
See 4 more Smart Citations
“…This demonstrates how difficult it is to stop this habit once it is established. Other studies in Saudi Arabia 8,11,13 reached similar conclusions. A study from British General Practice 35 reported an annual cessation rate ranging from 5% to 11% following simple advice and educational leaflets.…”
Section: 22supporting
confidence: 75%
“…The important role of doctors as a source of information on smoking hazards found in this study is inconsistent with other Saudi surveys, 8,12,13 probably because this study was conducted in a PHCC. The limited role of schools as a source of knowledge about smoking hazards was repeatedly found in previous surveys in this country among both the male 13 and female populations.…”
Section: 22contrasting
confidence: 55%
See 3 more Smart Citations